2013
DOI: 10.3201/eid1910.130609
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Influenza A Virus H7 and N9 Subtypes, Eastern Asia

Abstract: Influenza A viruses are a threat to poultry and human health. We investigated evolution of influenza A virus H7 and N9 subtypes in wild and domestic birds. Influenza A(H7N9) virus probably emerged after a long silent circulation in live poultry markets in eastern Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…H5N1 circulates in wild birds and infects poultry in backyards and small farms. In contrast, the 2013 H7N9 in China appears to have been generated relatively recently through reassortment and has not been found to any significant degree in wild birds, in waterfowl, or on rural farms (9,10). These data suggest that contamination of LPMs and bird-tobird transmission of H7N9 in these markets may be the primary initial mechanisms for amplifying transmission of the virus.…”
Section: Exposure To Live Poultry Marketscontrasting
confidence: 49%
See 1 more Smart Citation
“…H5N1 circulates in wild birds and infects poultry in backyards and small farms. In contrast, the 2013 H7N9 in China appears to have been generated relatively recently through reassortment and has not been found to any significant degree in wild birds, in waterfowl, or on rural farms (9,10). These data suggest that contamination of LPMs and bird-tobird transmission of H7N9 in these markets may be the primary initial mechanisms for amplifying transmission of the virus.…”
Section: Exposure To Live Poultry Marketscontrasting
confidence: 49%
“…Many of these reassortment events may have occurred in China over the three to four years prior to recognition of H7N9. Through use of conventional and next-generation sequencing methods, investigators revealed a complicated path of the virus' origin in Asia where LPMs likely served as a common mixing location for avian influenza virus reassortment (9,10). These genetic analyses were made possible through global agreement on sequence data sharing in the Global Initiative on Sharing Avian Influenza Data, an open gene sequence repository promoting fair access and use of influenza information (11).…”
Section: Virus Characteristicsmentioning
confidence: 99%
“…Bahl et al, 2009). However, for H7 IAVs, no major intercontinental gene flow has occurred during the past century between Eurasia and North America, suggesting that waterfowl migrations have not led to contemporary establishment of foreign origin H7 gene segments in the eastern and western hemispheres (Lebarbenchon & Stallknecht, 2011;Lebarbenchon et al, 2013). In North America, H7 and N9 viruses have circulated in wild birds with little evidence for genetic structure associated to the bird species nor location, supporting regular host species shifts (Chen & Holmes, 2009) and gene flow between North American migratory flyways (Lam et al, 2012;Bahl et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…IAVs of the H5 and H7 subtypes have the added potential of becoming highly pathogenic (HP), which can result in significant mortality and economic losses in domestic poultry. Additionally, the recent zoonosis of H7N9 IAV in China has raised concerns about the maintenance of H7 LP IAVs in domestic birds and the risks for spill-over into mammalian hosts, including humans Jonges et al, 2013;Lam et al, 2013;Lebarbenchon et al, 2013). In North America, there have been multiple detections of H7 IAVs in domestic poultry, including H7N2 LP IAVs that circulated in live-bird markets in the northeastern US for~13 years Spackman et al, 2003;Lebarbenchon & Stallknecht, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the average age was 20.8 years (14 months-75 years) in female cases, of which the reproductive age groups (20-45) accounted for 46.1% (130/282) of the female cases [17]. Additionally, the average age was 24.8 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years in the 15 pregnant women infected with the H5N1 virus. See Figure 2B and Table 1.…”
Section: Age and Sex Distributionmentioning
confidence: 98%